2016
DOI: 10.1016/j.ultsonch.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of the effect of liquid temperature on the sonolytic degradation of some organic dyes in water

Abstract: This paper presents a comprehensive experimental and numerical investigation of the effects of liquid temperature on the sonochemical degradation of three organic dyes, Rhodamine B (RhB), Acid orange 7 (AO7) and Malachite green (MG), largely used in the textile industry. The experiments have been carried out for an ultrasonic frequency of 300 kHz. The obtained experimental results were discussed using a new approach combining the results of single-bubble event and the number of active bubbles. The single-bubbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…The overall production rates (from multibubble system) of free radicals as well as the conditions of the bubble collapse (bubble temperature) have been estimated under the experimental conditions of this study using a theoretical procedure based on single bubble theory, which has been fully described in our previous work [35]. The production rate of each radical formed during the bubbles implosion is calculated as r i = n i ×N, where n i is the number of moles of the radical i, i.e.…”
Section: Theoretical Packagementioning
confidence: 99%
“…The overall production rates (from multibubble system) of free radicals as well as the conditions of the bubble collapse (bubble temperature) have been estimated under the experimental conditions of this study using a theoretical procedure based on single bubble theory, which has been fully described in our previous work [35]. The production rate of each radical formed during the bubbles implosion is calculated as r i = n i ×N, where n i is the number of moles of the radical i, i.e.…”
Section: Theoretical Packagementioning
confidence: 99%
“…Similarly, the relationship between OH . yield and the parameters d 0 , N hole are: (15) For d p , it is found that the linear correlations from data fitting is:…”
Section: Development Of a Correlation For Design Of Cavitation Structurementioning
confidence: 99%
“…This investigation is of great significance to address the mechanism of free radical generation, but it relates to single acoustic cavitation bubbles without considering radical diffusion. Merouani et al carried out a series of chemical reactions inside collapsing acoustic bubbles, which gave deep insight into the chemistry of the cavitation phenomena. They developed a novel approach to determine the number of active bubbles using a semi‐empirical model based on the material balances for H 2 O 2 , OH • , and HO 2 · in the liquid phase and creatively estimated the overall production rate of OH • .…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic irradiation has shown promise for the purification of contaminated water (or textile effluents) and involves at least in significant part standard hydroxyl radical mediated chain oxidation processes [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Versatility of ultrasonic irradiation should make it adaptable for the removal of problematic contaminants in aqueous phase. Despite the tremendous interest in the ultrasonic irradiation induced degradation of pollutants, much of the fundamental understanding and characterization of these complex processes are still at the preliminary stages [24][25][26]29].…”
Section: Introductionmentioning
confidence: 99%